CORRELATION OF MARKETING STRATEGIES AND SCHOOL QUALITY WITH COMMUNITY INTEREST IN CHOOSING SCHOOLS AS CHILD EDUCATION INSTITUTIONS - Nurul Hidayah (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2019)
Abstract: This research is a field research study with a quantitative approach to statistical analysis and explanatory descriptive analysis. Data analysis uses multiple correlations which are processed using the SPSS application. The results showed that (1) the level of madrasah marketing strategy in marketing madrasah programs in Mataram City was 72.31% (good), while the correlation was 0.257 (weak), because it was only influenced by 6.61% and 93.31% influenced by other factors; (2) the quality level of the madrasah as a child education institution in Mataram City is 74.24% (good), while the correlation is 0.323 (weak) because it is only affected by 10.43% and 89.57% is influenced by other factors; (3) the level of public interest in the city of Mataram in choosing madrasah as children's educational institutions by 75.68% (good); (4) there is a correlation between madrasah marketing strategy and madrasah quality with public interest in choosing madrasah as a children's educational institution that is equal to 0.387 (weak) because it is only influenced by 15%, while 85% is influenced by other factors. Factors that influence the weak correlation of madrasah marketing strategies and the quality of madrasah with the public interest in choosing madrasah as children's educational institutions are consumer behavior which includes psychological aspects, cultural aspects, economic aspects and aspects of personal decisions.Abstrak: Penelitian ini adalah penelitian studi lapangan dengan pendekatan kuantitatif untuk analisis statistik dan deskriptif. Analisis data menggunakan beberapa korelasi yang diproses menggunakan aplikasi SPSS. Hasil penelitian menunjukkan bahwa (1) tingkat strategi pemasaran Madrasah dalam pemasaran program Madrasah di Kota Mataram adalah 72,31% (baik), sedangkan nilai korelasinya sebesar 0,257 (lemah), karena hanya dipengaruhi oleh 6,61% dan 93,31% dipengaruhi oleh faktor lain; (2) tingkat kualitas Madrasah sebagai lembaga pendidikan anak di Kota Mataram adalah 74,24% (baik), sedangkan korelasinya sebesar 0,323 (lemah) karena hanya dipengaruhi oleh 10,43% dan 89,57% dipengaruhi oleh faktor lain; (3) tingkat kepentingan publik di Kota Mataram dalam memilih Madrasah sebagai lembaga pendidikan anak-anak sebesar 75,68% (baik); (4) terdapat korelasi antara strategi pemasaran Madrasah dengan mutu Madrasah dengan kepentingan masyarakat dalam memilih Madrasah sebagai lembaga pendidikan anak yang setara dengan 0,387 (lemah) karena hanya dipengaruhi oleh 15%, sedangkan 85% dipengaruhi oleh Faktor. Faktor yang mempengaruhi korelasi yang lemah dari strategi pemasaran Madrasah dan mutu Madrasah dengan kepentingan masyarakat dalam memilih Madrasah sebagai lembaga pendidikan anak adalah perilaku konsumen yang meliputi aspek psikologis, budaya aspek ekonomi dan aspek keputusan pribadi.